2012
DOI: 10.4055/cios.2012.4.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Lesions in Chronic Lateral Ankle Instability: Comparison of Arthroscopy with Magnetic Resonance Imaging Findings

Abstract: BackgroundChronic lateral ankle instability often accompanies intra-articular lesions, and arthroscopy is often useful in diagnosis and treatment of intra-articular lesions.MethodsPreoperative magnetic resonance imaging (MRI) examinations and arthroscopic findings were reviewed retrospectively and compared in 65 patients who underwent surgery for chronic lateral ankle instability from January 2006 to January 2010. MR images obtained were assessed by two radiologists, and the inter- and intra-observer reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 21 publications
1
57
2
Order By: Relevance
“…17,18 Other studies found intra-articular lesions on arthroscopy in 90-97% of the patients seen in secondary care. 19,20 The percentages of abnormalities found in these latter studies are much higher compared with those of the present study. Although this difference could be attributed to the techniques applied, it is most likely caused by the different study populations.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 54%
See 1 more Smart Citation
“…17,18 Other studies found intra-articular lesions on arthroscopy in 90-97% of the patients seen in secondary care. 19,20 The percentages of abnormalities found in these latter studies are much higher compared with those of the present study. Although this difference could be attributed to the techniques applied, it is most likely caused by the different study populations.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 54%
“…Although this difference could be attributed to the techniques applied, it is most likely caused by the different study populations. 20 In addition to the frequent abnormalities found in the ligaments, structural damage was also frequently seen in the bone and cartilage. Most apparent are the findings in the talocrural and talonavicular joints.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…In the literature, the accuracy in the detection of cartilage lesions of the knee has been reported to be as high as 87% at 1.5 T and 90% at 3.0 T [21]. For MR imaging of the ankle, sensitivity in detection of cartilage lesions varied between 50% at 1.5 T and 75% at 3.0 T [5,6]. A slightly higher sensitivity was found for MR arthrography (MRA) and computed tomography arthrography (CTA) [22].…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to the knee, articular cartilage at the hip and at the ankle is relatively thin (about 1.2-2.4 mm) [20]. On standard MR imaging of the ankle, usually, there is direct contact between the cartilage of both articulating surfaces, thus these surfaces are commonly difficult to evaluate [5]. In the literature, the accuracy in the detection of cartilage lesions of the knee has been reported to be as high as 87% at 1.5 T and 90% at 3.0 T [21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation